Synergistic dual ring-cleavage pathways enable efficient degradation of chlorobenzenes by Pseudomonas putida BS-1 in groundwater - Ji Ouyang; Yuke Luo; Fei Gu; Yan Zhou; Changzheng Cui (Journal of Hazardous Materials, 2026)

Evaluation of seismic performance of prefabricated underground mid-partition walls connected by UHPC grouting sleeves - Zhen Huang; Yuke Luo; Caichao Wei; Bin Liu; Ning Li; Jianguo Dang; Zhanshuo Yan (Tunnelling and Underground Space Technology, 2026)

Chlorine-resistant bacteria in drinking water system: Detection characteristics, identification, and chlorine resistance mechanisms - Chicheng Yan; Xuan Ni; Yuke Luo; Ziwei Han; Bingbing Guo; Changzheng Cui (Journal of Hazardous Materials, 2026)

Soil aggregates stability is evidently enhanced by super-binding of the N-terminal disordered tail of glomalin to soil minerals - Minghui Jia; Youchao Wang; Jin He; Shan-Ho Chou; Dehua Luo; Linchuan Fang; Jingtao Hou; Yuke Fan; Wenjun Zhang; Hansong Chen; Dejian Zhou; Yurong Liu; et al. (Soil Biology and Biochemistry, 2025)

Stability Analysis of Cracked Clay Slopes Using a Modified Mohr–Coulomb Criterion - Yukuai Wan; Gui Luo; Yuke Wang; Fei Zhang; Hong Guan (Geotechnical and Geological Engineering, 2025)

Evaluation on the thermal and optical performance of a double skin facade with a semi-transparent phase change material blind system - Yilin Li; Wanting Tao; Zewen Liu; Yuke Peng; Lulu Zhu; Hao Lu; Aiwei Luo; Weiguang Su; Feng Deng (Energy and Buildings, 2025)

PM2.5-bound polycyclic aromatic hydrocarbons (PAHs) in urban Beijing during heating season: Hourly variations, sources, and health risks - Yu Wang; Zhaojin An; Youhua Zhao; Hao Yu; Dongbin Wang; Guodong Hou; Yuke Cui; Wuyue Luo; Qianhe Dong; Pengtuan Hu; Leicheng Zhao; Zhiguo Cao; et al. (Atmospheric Environment, 2025)

Spatio-temporal patterns of temperature extremes and their response to atmospheric circulation factors in China from 1961 to 2020 - Yuanbo Luo; Yuke Zhou; Chenghu Zhou (Journal of Geographical Sciences, 2024)

Arsenic field test kits based on solid-phase fluorescence filter effect induced by silver nanoparticle formation - Wenhui Yang; Liqing Ye; Yuke Wu; Xi Wang; Simin Ye; Yurong Deng; Ke Huang; Hong Luo; Jinyi Zhang; Chengbin Zheng (Journal of Hazardous Materials, 2024)

Exceptional anti-toxic growth of water spinach in arsenic and cadmium co-contaminated soil remediated using biochar loaded with Bacillus aryabhattai - Yutian Huang; Ting Liu; Jie Liu; Xiao Xiao; Yuke Wan; Huanhuan An; Xubiao Luo; Shenglian Luo (Journal of Hazardous Materials, 2024)

Insight of persulfate-based treatments induced stable volatile fatty acids promotion during waste activated sludge anaerobic fermentation in semi-continuous-flow reactors: Focusing on variations of substrate and microbial functional profiles - Qin Zhang; Yuke Xu; Wenzhuo Li; Yiyun Liu; Zailiang Liu; Jun Zheng; Huijuan Zhang; Jingyang Luo (Journal of Cleaner Production, 2024)

Construction of an S-scheme Ce/Ti-MOFs heterojunction with abundant Oxygen vacancies (Ovs) for efficient charges separation: Performance and mechanism insight - Chentao Hou; Yi Liu; Yijie Li; Yuke Xie; Peiyan Luo; Mingyuan Zhang; Liping Wang (Journal of Water Process Engineering, 2023)

Bioleaching and immobilizing of copper and zinc using endophytes coupled with biochar-hydroxyapatite: Bipolar remediation for heavy metals contaminated mining soils - Weiran Feng; Xiao Xiao; Junjie Li; Qicheng Xiao; Li Ma; Qifeng Gao; Yuke Wan; Yutian Huang; Ting Liu; Xubiao Luo; Shenglian Luo; Guisheng Zeng; et al. (Chemosphere, 2023)

Monitoring nature's calendar from space: Emerging topics in land surface phenology and associated opportunities for science applications - Xuanlong Ma; Xiaolin Zhu; Qiaoyun Xie; Jiaxin Jin; Yuke Zhou; Yunpeng Luo; Yuxia Liu; Jiaqi Tian; Yuhe Zhao (Global Change Biology, 2022)
Vegetation phenology has been viewed as the nature's calendar and an integrative indicator of plant‐climate interactions. The correct representation of vegetation phenology is important for models to accurately simulate the exchange of carbon, water, and energy between the vegetated land surface and the atmosphere. Remote sensing has advanced the monitoring of vegetation phenology by providing spatially and temporally continuous data that together with conventional ground observations offers a unique contribution to our knowledge about the environmental impact on ecosystems as well as the ecological adaptations and feedback to global climate change. Land surface phenology (LSP) is defined as the use of satellites to monitor seasonal dynamics in vegetated land surfaces and to estimate phenological transition dates. LSP, as an interdisciplinary subject among remote sensing, ecology, and biometeorology, has undergone rapid development over the past few decades. Recent advances in sensor technologies, as well as data fusion techniques, have enabled novel phenology retrieval algorithms that refine phenology details at even higher spatiotemporal resolutions, providing new insights into ecosystem dynamics. As such, here we summarize the recent advances in LSP and the associated opportunities for science applications. We focus on the remaining challenges, promising techniques, and emerging topics that together we believe will truly form the very frontier of the global LSP research field.

Uranium and graphite mineralization in metamorphic rocks in the Kangding complex (Datian area), southwestern Yangtze Platform, Western China - Long Cheng; Dejiang Luo; Chengjiang Zhang; Yuke Wang (Arabian Journal of Geosciences, 2022)

Effects of l-carnitine against H2O2-induced oxidative stress in grass carp ovary cells (Ctenopharyngodon idellus) - Qiuju Wang; Xue Ju; Yuke Chen; Xiaoqing Dong; Sha Luo; Hongjian Liu; Dongming Zhang (Fish Physiology and Biochemistry, 2016)